Comparative evaluation of 99mTc-Al2o3 and 99mTc-fitatnanocolloids for sentinel lymph nodes vizualisation in patients with cancer of larunx and hypopharynx - Chernov V. I. Vladimir Ivanovich; Sinilkin I. G. Ivan Gennadjevich; Choynzonov E. L. Evgeny Lkhamatsyrenovich; Chizhevskaya S. Yu. Svetlana Yurjevna; Titskaya А. А. Anna Aleksndrovna; Zelchan (Zeltchan) R. V. Roman Vladimirovich; Bragina O. D. Olga Dmitrievna; Lyapunov A. Yu. Aleksandr Yurjevich; Skuridin V. S. Viktor Sergeyevich (2015, 2015)
Title screen